SERVICE TO THE COMMUNITY COVID-19 DISASTER VOLUNTEERS (PKM-BC19) IN LIMAU MANIS SELATAN VILLAGE, PAUH SUBDISTRICT, PADANG CITY, WEST SUMATRA PROVINCE - Yenrina, Rina; Pratiwi, Nori (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2022)
Community Service disaster Covid-19 (PKM-BC19) is the theme of activities in this pandemic period carried out by students accompanied by lecturers. Students as covid-19 volunteers to help the community know covid-19 and the symptoms it causes, how to prevent it, so that the community is more careful and protect themselves from the virus that is currently spreading. Activities are carried out in their respective residences and help the community in accordance with health protocols that apply in their respective regions. The location of the implementation in Limau Manis Selatan Village, Pauh Subdistrict, Padang City, West Sumatra Province. The work program implemented includes main activities, supporting activities and multimedia activities or additional activities. The main activities are activities related to Covid-19. Supporting activities are activities related to the economy, environment, social and education to the community. Multimedia activities or additional activities such as making tutorial videos or educational videos that are then uploaded to social media such as Youtube and Instagram.